Clinical, Laboratory Aspects and Management of Factor X Deficiency - Menegatti, Marzia; Peyvandi, Flora (Seminars in Thrombosis and Hemostasis, 2024)
Coagulation factor X (FX), originally named Stuart–Prower factor, plays a pivotal role in the coagulation cascade, activating thrombin to promote platelet plug formation and prevent excess blood loss. Genetic variants in F10 may lead to FX deficiency and to impaired coagulation. FX variants are phenotypically classified as being type I, with the concomitant reduction of FX coagulant activity and FX antigen levels or type II, corresponding to a reduction in activity with normal antigen plasma levels. Patients affected with FX deficiency tend to be one of the most seriously affected among those with rare bleeding disorders. They show a variable bleeding tendency strongly associated with FX coagulant activity levels in plasma and may present, in the severe form of the deficiency, life-threatening symptoms such as gastrointestinal and umbilical stump bleeding and intracranial hemorrhages or central nervous system bleeding. Treatment of FX deficiency was originally based on the replacement of the missing factor using fresh frozen plasma, cryoprecipitate and prothrombin complex concentrates; however, a plasma-derived concentrate, shown to be safe and effective in clinical trials, is now available. In addition, novel nonreplacement therapy such as small interference RNA, gene therapy, drug repurposing, and gene editing may also represent novel therapeutic approaches for FX deficiency, but further, much focused studies are needed before considering this emerging therapy in such patients.
Keywords: bleeding disorders; factor X; factor X deficiency; gene mutations; replacement therapy